Temperature-Induced Environmental Chain Reaction in Marine Sedimentation and Its Impact on Manila Clam Ruditapes philippinarum - Liu, Yi; Zhang, Jihong; Wang, Xinmeng; Wu, Wenguang; Kang, Qinzi; Li, Chaolun (Frontiers in Marine Science, 2022)
Marine Heatwave (MHW) events have been increasing, causing severe impacts on marine ecosystems and aquaculture. In this study, the effects of temperature on changes in sediment dissolved oxygen(DO) and hydrogen sulfide (H2S) concentrations and their effects on the behavioral and physiological responses of a bivalve were investigated by simulating different sudden summer temperature change conditions. The results showed that temperature was an important factor affecting DO consumption and H2S release in sediments, and sediment type also played a key role. At higher temperatures, DO was consumed more rapidly and H2S release increased in sediments, and the DO was consumed and H2S released in sandy sediments was less than in silty sand sediments. The response of Manila clam’s exercise behavior under environmental pressure was also rapid. The excavation index of the Manila clam decreased with the DO consumption, indicating that the Manila clam could alter its burial depth and move towards the sediment-water interface when stressed. Compared with PO activity being activated under experimental conditions, succinate concentrations only increased slightly at 32 °C, and did not surpass the threshold indicative of anaerobic metabolism. However, when toxic substances such as H2S start to accumulate, they may damage the immune system and tissues of the Manila clam, thereby affecting its future survival. Therefore, when temperatures are high for long periods in summer, it is necessary to take timely action to prevent and guard against harm caused by DO and H2S to aquaculture organisms.